De la imagen del poder al poder de la imagen.: A propósito de la heráldica de Alonso de Fonseca II y Acevedo - Herrera Vicente, Javier (Eikón / Imago, 2025)
This study analyses the heraldry of D. Alonso de Fonseca II y Acevedo (c.a.1437-1512) in the church of San Benito in Salamanca. The coats of arms presented in this article are not an addition that is only limited to identifying the lineage and ornamenting the perimeter walls of the church; on the contrary, they are ontologically linked to a persuasive strategy implemented by their promoter. The aim is to understand how the archbishop began to work on the creation of an ostentatious personal image in accordance with his religious dignity at the beginning of the 16th century. From this point of view, it is understood that these objects not only represent the power, it also presents to the spectator as "living" artefacts with a specific purpose. Therefore, this article focuses on the symbolic potential of coat of arms and examines the relationship between the Salamanca context, the San Benito church, the heraldic pieces, and their reception.